Air-liquid interface biofilm formation of pseudomonads and the impact of traditional clean-in-place on biofilm removal - Muthuraman S; Palmer J; Flint S (Elsevier Ltd, 2026)
Pseudomonads are common psychrotrophic spoilage bacteria associated with dairy, poultry, and meat processing environments. They can multiply at low temperatures, 4–7 °C, producing thermostable spoilage enzymes. Pseudomonads form strong biofilms by producing higher EPS (Extracellular polymeric substances) at low temperatures. This study focused on the biofilm formation of pseudomonads at the air-liquid interface and their EPS removal. Two strong biofilm-forming isolates, (Pseudomonas lundensis) 3SM and (Pseudomonas cedrina) 20SM were allowed to form biofilms on stainless steel coupons in a CDC reactor under a continuous flow of nutrients at 4 °C over a week. The cell counts reached approximately 7.5 log CFU/cm2. The biofilms formed at the air-liquid interface showed more visible biofilms, polysaccharides, and higher cell counts than those submerged in liquid. Cleaning the biofilms using 1 % NaOH at 70 °C resulted in viable bacterial cells below the detection limit. However, residual material termed biofilm “footprints” was present after cleaning and were analysed with SEM and FTIR. The SEM observations showed tightly packed robust biofilm cells before cleaning. Coupons treated with 55 °C water showed an upper layer of degraded cells. After treatment with 70 °C NaOH, organic material was still visible under SEM. Based on the FTIR observations, the EPS extracted from the control and treated coupons showed that the amount of biomolecules reduced after cleaning with NaOH, but the footprints still existed. The biofilm footprints led to the early appearance of biofilms at the air-liquid interface compared to new coupons exposed to strong biofilm-forming isolates. Cleaning with caustic can eliminate the cells, but the EPS from biofilms of pseudomonads is not completely removed, resulting in a possibility of regrowth when the new inoculum is introduced.
Keywords: Pseudomonads; Biofilm; EPSCIP process; Regrowth; Footprints